Pelepasan Bahan Aktif Bertahan Lama dari Briket Cetakan Urea - Muslim Suardi; Martin Suhendri; Winarsih Tiara (Jurnal Ilmu Kesehatan Abdurrab, 2025)
The limitations of conventional urea fertilizers are the high their solubility, inefficient use, and environmental impact. The objective of the study was to formulate the long-lasting urea slow-release fertilizer (SRF) in briquette form following the molding method. The briquettes were prepared using polystyrene (PS) and starch (ST) bioblend in three formulas. The ratios of urea to bioblend in Formulas 1, 2, and 3 were 1.5:1, 1:1, and 1:1.5, respectively. However, the ratios between PS and ST in Formulas 1, 2, and 3 were 3:1, 4:1, and 5:1, respectively. Urea levels in the briquette and in the dissolution medium were analyzed using a visible spectrophotometer. Urea was reacted by the addition of Ehrlich reagents. The absorbance of the solution was measured at a maximum absorption wavelength of 420 nm. The dissolution efficiency of urea from Formula 1, 2, and 3 was 34.84±0.52, 32.55±0.91, and 30.76±0.39%, respectively (p˂0.05). The release kinetics of urea from the briquette followed the Korsmeyer-Peppas model. The T90 from all of the formulas obtained in the range of 8.3 to 12.9 years. It is an extraordinary long lasting fertilizer release.